Organizational Performance Improvement Strategies Through Organizational Learning and Employee Empowerment: Organizational Commitment as Mediation - Imam, Sabferrial Fernando; Riyanto , Setyo; Santoso , Sugeng; Ramli , Yanto (ADPEBI International Journal of Business and Social Science, 2024)
Purpose – Organizational performance is heavily influenced by human resources in government administration, including resource allocation for individual work in all organizations. Organizational performance can be improved by ensuring that each level in the organization meets the job requirements and has a clear plan to support the achievement of organizational goals. Methodology/approach – This research uses quantitative research and uses structural equation modeling analysis (SEM) with Partial Least Squares (PLS) software. The study has a population of 50 officials who support the planning and performance measurement of the regional government unit of the province of Banten. Findings – The result is that learning organization has a direct impact on organizational commitment, while learning organization has no impact on organizational performance. Employee empowerment affects organizational commitment and organizational performance. Organizational commitment influences organizational performance. Organizational commitment does not mediate between learning organization and organizational performance, but may mediate between employee empowerment and organizational performance. Novelty/value – Learning organization and employee empowerment promote sustainable improvement, innovation, and adaptability, and empower employees to make the right decisions and contribute to organizational goals. It fosters commitment, emotional attachment, and productivity, enabling organizations to adapt and maintain competitive advantage.